UPPB INSTITUTIONAL PERFORMANCE ANALYSIS ON RUBBER TRADING SYSTEM IN SOUTH SUMATERA - Novayanti Novayanti; Fifian Permata Sari; Achmad Tarmizi; Anggi Fatmayati (International Journal of Social Science, 2023)
Analysis of the institutional performance of the Bokar Processing and Marketing Unit (UPPB) in the rubber trading system in South Sumatra. The purpose of this study was to analyze the institutional performance of UPPB in the rubber trading system in South Sumatra. UPPB's institutional performance on the rubber trading system in South Sumatra is influenced by the characteristics of farmers, institutional characteristics, institutional leadership, values, and governance (autonomy of administration) of the local government. Meanwhile, the physical and social environment of farmers, institutional leadership and social organization did not affect the institutional performance of UPPB. In addition, the institutional performance of UPPB affects the level of farmers' welfare. When institutional performance increases, the level of farmer welfare also increases and vice versa.